2019
DOI: 10.3171/2018.4.jns172148
|View full text |Cite|
|
Sign up to set email alerts
|

Developing an optimal follow-up strategy based on the natural history of nonfunctioning pituitary adenomas

Abstract: OBJECTIVE The natural history and proper algorithm for follow-up testing of nonfunctioning pituitary adenomas (PAs) are not well known, despite their relatively high prevalence. The aim of this study was to suggest the optimal follow-up algorithm for nonfunctioning PAs based on their natural history. METHODS The authors followed up 197 patients with nonfunctioning PAs that had not been treated (including surgery and radiation therapy) at the time of detection, in a single center, between March 2000 and Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Selected patients with slowly progressive visual loss, functioning tumors with aggressive clinical features, and those with an unclear diagnosis, may also benefit from urgent (but not emergent) surgery, with decisions made on a case-by-case basis. Patients with incidental and asymptomatic tumors, known nonfunctioning adenomas [7] or functioning tumors, which are well controlled with medical therapy, can be scheduled as elective cases.…”
Section: Recommendations For Pituitary Surgerymentioning
confidence: 99%
“…Selected patients with slowly progressive visual loss, functioning tumors with aggressive clinical features, and those with an unclear diagnosis, may also benefit from urgent (but not emergent) surgery, with decisions made on a case-by-case basis. Patients with incidental and asymptomatic tumors, known nonfunctioning adenomas [7] or functioning tumors, which are well controlled with medical therapy, can be scheduled as elective cases.…”
Section: Recommendations For Pituitary Surgerymentioning
confidence: 99%
“…With the exception of prolactinomas, which are treated with dopamine agonists, most pituitary tumors undergo surgical resection as first-line treatment [67]. Approximately 80% of nonfunctioning and GH-secreting and 25% of PRL-secreting adenomas are macroadenomas (≥1 cm in diameter) at presentation [68]. These tumors often invade surrounding structures, including the cavernous sinus or dura mater, and incomplete resection is common with reported cure rates of 30%, even in specialized centers [69].…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…If non-secretor microadenomas may be assessed every 1 year and then every 2-3 years, the first assessment for a macroadenoma is needed after 6 months during the first 2-3 years and then yearly if the tumour is stationary (20,21). One study found that a volume growth more than 0.88 cm3/year at magnetic resonance imagery allows the rescan after 2 years while less than mentioned cut off indicates a rescan after 4 years (22). The natural history of pituitary macroadenomas conservatory treated is still a heterogeneous topic (20)(21)(22).…”
Section: Optimal Strategy Of Macroadenomas Follow-upmentioning
confidence: 99%
“…One study found that a volume growth more than 0.88 cm3/year at magnetic resonance imagery allows the rescan after 2 years while less than mentioned cut off indicates a rescan after 4 years (22). The natural history of pituitary macroadenomas conservatory treated is still a heterogeneous topic (20)(21)(22).…”
Section: Optimal Strategy Of Macroadenomas Follow-upmentioning
confidence: 99%